Relationship Between Selected Factors of Job Satisfaction and Job Performance Among Workers at Palm Oil Industries - Rusli, Ahmad; HII, EE ING; Sopian, Bujang (International Review of Management and Business Research (IRMBR, 2014)
This study aims to identify the relationship between selected factors of job satisfaction and job performance. The factors of job satisfaction that examine in this study are including pay, work itself, promotion, supervision, and co-workers. The research instrument for this study was used questionnaire to collect data from the respondents. This study was conducted at two oil palm industries, which located in Sibu, Sarawak, Malaysia. 100 sets of the questionnaires were distributed to the employees in oil palm industry. However, only 81 sets of the questionnaires were successfully collected. The data that collected were analyzed through Statistical Package for Social Sciences (SPSS) version 17.0. Pearson Correlation Analysis used to identify the relationship between the selected factors of job satisfaction and job performance. The findings in this study indicated that there is significant relationship between selected factors of job satisfaction and job performance. Through the findings, the organization and human resource practitioners were recommended to understand and satisfy employees’ needs in order to improve employees’ job performance in oil palm industry.